2020
DOI: 10.7717/peerj.9180
|View full text |Cite
|
Sign up to set email alerts
|

Developments in marine invertebrate primary culture reveal novel cell morphologies in the model bivalve Crassostrea gigas

Abstract: Cell culture provides useful model systems used in a wide range of biological applications, but its utility in marine invertebrates is limited due to the lack of immortalised cell lines. Primary cell and tissue cultures are typically used but remain poorly characterised for oysters, which can cause issues with experimental consistency and reproducibility. Improvements to methods of repeatable isolation, culture, and characterisation of oyster cells and tissues are required to help address these issues. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
(69 reference statements)
2
17
0
Order By: Relevance
“…The morphology of cultured scallop cells varied among organs. In both types of gonadal cells, most cultured cells were fibroblast-like, consistent with previous findings [9]. In this study, round adhered cells and spread adhered cells were also observed in female gonadal cell culture.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The morphology of cultured scallop cells varied among organs. In both types of gonadal cells, most cultured cells were fibroblast-like, consistent with previous findings [9]. In this study, round adhered cells and spread adhered cells were also observed in female gonadal cell culture.…”
Section: Discussionsupporting
confidence: 92%
“…The spread adhered cells may be immune cells, since they had morphology similar to confluent granulocytes in C. gigas cultured heart cells [9]. Adductor muscular cells have multiple filopodia.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations